An Afro-Christian ministry to people living with HIV / Aids in South Africa - Manala, Matsobane J. (HTS : Theological Studies, 2005)
The HIV / Aids pandemic is cause for great frustration to the developing countries in their attempts to improve the quality of life of their citizens. HIV / Aids in South Africa demands a specific approach to the Christian ministry in which the African world-view is acknowledged. In order for the church to play a relevant and meaningful role in combating the HIV / Aids pandemic, it is necessary that the church should be informed of the existential situation of persons living with HIV / Aids. This information is vital for raising awareness and engendering sensitivity among Christians. In the context of such awareness of and sensitivity to human pain and suffering, the community of the faithful should be moved to heed Christ's call to show neighbourly love. The possible role of the church in caring for those who are already infected with HIV is defined.
Free